Feeding habits and ontogenic changes in digestive enzyme patterns in five freshwater teleosts - M. M. Solovyev; E. N. Kashinskaya; G. I. Izvekova; E. Gisbert; V. V. Glupov (Journal of Fish Biology, 2014)
Feeding habits and the activity of digestive enzymes (total alkaline proteases, α ‐amylase and lipase) from dace Leuciscus leuciscus , roach Rutilus rutilus , Prussian carp Carassius auratus gibelio , perch Perca fluviatilis and pikeperch Sander lucioperca fry were studied in the Malye Chany Lake–Kargat Estuary (western Siberia, Russia). The diet of fry from all studied species was mainly composed of chironomid larvae and zooplanktonic organisms ( i.e. cladocera and copepoda), whereas carnivorous species such as P. fluviatilis and S. lucioperca also preyed on fry from other fishes while detritus and microalgae were also important in the diet of ommivorous species. When comparing diet similarity (Sørensen–Dice index, Q S ) among fry at different stages of development, both omnivorous and carnivorous species showed a high level of similarity (0·67 Q S Q S α ‐amylase:total proteases (A:P) values higher than 1 in omnivorous species and lower (A:P ≤ 1) in carnivorous species.